Novel Schiff Bases of C-Methylresorcinarene Derivatives - Albina Y. Ziganshina; Olga S. Saranova; Rezeda R. Fazleeva; Vitaly V. Yanilkin; Igor S. Antipin (Molbank, 2022)
The article presents the synthesis and properties of two new Schiff bases of resorcinarene derivatives. The Schiff bases were obtained by the reaction of formylresorcinarene with aromatic (o-aminophenol) and aliphatic (N,N-dimethyldiaminoethane) amines in chloroform. The synthesized Schiff bases exist in equilibrium of several tautomers, as evident from the IR, UV, NMR spectra and cyclic voltammetry data analysis. In DMF, methanol, and acetonitrile, the tautomeric equilibrium is shifted toward the enol-imine tautomers.